Real world Adobe Photoshop CS3 : industrial-strength production techniques - Blatner, David (Peachpit Press, 2008)
Anyone who relies on Photoshop to meet tough production challenges knows that when a new version arrives, especially one as chockfull of enhancements as Photoshop CS3, there's no time to fool around. You need to get up to speed on it, and you need to do so now. This book will get you there. In this copiously illustrated book, best-selling author David Blatner offers shows you how to sharpen your Photoshop production techniques and provides clear explanations of the concepts that drive them. Readers will learn about managing color, correcting colors, capturing images, getting great scans, and more. They'll also find complete coverage of Photoshop CS3's new features: a streamlined interface, nondestructive Smart Filters, a new Quick Selection and Refine Edge tools, improved Curves, automatic layer alignment and blending, and more. Throughout, the emphasis in this book is on efficiency: the timesaving tips and professional shortcuts that will allow readers to solve their everyday production challenges creatively with Photoshop CS3.